Epidemiological survey for dental trauma among 12-year-old children in Erbil City, Iraq - Mohamed Salim Younus; Karam Ahmed (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Dental injury and trauma are some of the most important public health concerns among school children that may require immediate management, as they could result in consequences affecting the child aesthetically, psychologically and socially. Purpose: The aim of this study was to determine the prevalence of dental trauma, the type of fracture, the most commonly affected tooth and the effect of gender on the occurrence of dental trauma. Methods: The methodology of this study was a cross-sectional survey consisting of a questionnaire and an oral examination which was conducted on 12-year-old public primary school children. Schools were selected from five different areas of Erbil city in Iraq. Results: The results indicate that 16.3% of the sample were affected with dental trauma in both genders. Maxillary central incisor was the most commonly affected tooth, and the majority of dental traumas were untreated. The most common type of dental trauma was simple enamel fracture. Conclusions: Child students are at great risk regarding dental trauma, which may affect their social activity especially within their school life.